Forestry: its present position and future prospects in Ireland - Muriel, C.E. (Statistical and Social Inquiry Society of Ireland, 1912)
In a most interesting paper read before this Society in November, 1903, by the late Mr. C. Litton Falkiner, the forestry question was considered historically: in this paper I propose to discuss, chiefly with reference to Ireland, the most recent results of the consideration given to the present state of forestry, and proposals for its future, which are embodied in the Report of the Departmental Committee on Irish Forestry, published a year ago, and in the Afforestation Report of the Royal Commission, dealing generally for the United Kingdom with the subject of afforestation as a means of increasing employment during periods of depression in the labour market, which issued in January last.
Read, 23rd April, 1909.
Keywords: Forestry; Afforestation; 314.15